Multichannel transcranial direct current stimulation over the left dorsolateral prefrontal cortex may modulate the induction of secondary hyperalgesia, a double-blinded cross-over study in healthy volunteers - Steyaert, Arnaud; Lenoir, Cédric; Lavand’homme, Patricia; van den Broeke, Emanuel N.; Mouraux, André (PLOS ONE, 2022)
Background Central sensitization is thought to play a critical role in the development of chronic pain, and secondary mechanical hyperalgesia is considered one of its hall-mark features. Consequently, interventions capable of modulating its development could have important therapeutic value. Non-invasive neuromodulation of the left dorsolateral prefrontal cortex (DLPFC) has shown potential to reduce pain, both in healthy volunteers and in patients. Whether it can modulate the induction of central sensitization, however, is less well known. Objective To determine whether multifocal transcranial direct current stimulation (tDCS) targeting the left DLPFC affects the development of secondary mechanical hyperalgesia. Methods In this within-subjects, cross-over, double-blinded study, eighteen healthy volunteers participated in three experimental sessions. After 20 minutes of either anodal, cathodal, or sham multichannel tDCS over the left DLPFC, secondary mechanical hyperalgesia was induced using high-frequency electrical stimulation (HFS) of the volar forearm. We assessed intensity of perception to 128 mN mechanical pinprick stimuli at baseline and up to 240 minutes after HFS. We also mapped the area of mechanical hyperalgesia. Results HFS resulted in a robust and unilateral increase in the intensity of perception to mechanical pinprick stimuli at the HFS arm, which was not different between tDCS stimulation conditions. However, the area of hyperalgesia was reduced after anodal tDCS compared to sham. Conclusion Anodal tDCS over the left DLPFC modestly modulates the size of the HFS-induced area of secondary mechanical hyperalgesia, suggesting that non-invasive neuromodulation targeting the left DLPFC may be a potential intervention to limit the development of central sensitization.